Pendekatan Sosiologis Terhadap Konsep Absābun Nuzūl: Studi Kasus Ayat-Ayat Sosial Dan Pendidikan Dalam Konteks Kekinian - Hajjin Mabrur; Yusuf Maulana; Ravi Fairuz Zabadi (Indonesian Journal of Islamic Education Studies (INJURIES), 2026)
The understanding of Asbābun Nuzūl has traditionally focused on historical and textual narration, often detached from the social and educational dynamics underlying the revelation of Qur’anic verses. This study introduces a new perspective by applying a sociological approach to Asbābun Nuzūl, specifically examining verses related to social justice and education in the contemporary context. Using a qualitative method with sociological hermeneutics, this study reconstructs the social, cultural, and moral conditions of classical Arab society and connects them to present-day social and educational phenomena. Primary data include QS. Al-Hujurat [49]:13, QS. Al-Ma’un [107]:1–7, QS. An-Nisa [4]:135, and QS. Al-‘Alaq [96]:1–5, while secondary data are drawn from classical tafsir works and contemporary literature in sociology of religion and Islamic education. The findings reveal that Asbābun Nuzūl not only explains the occasions of revelation but also illustrates the interaction between the revealed text and social-educational structures. The sociological analysis demonstrates that Qur’anic values of equality, solidarity, justice, and the pursuit of knowledge are universal and remain relevant in addressing contemporary social problems and educational crises. This sociological approach expands the horizons of Ulūm al-Qur’ān from textual to contextual interpretation that is responsive to social reality and educational needs.